Neoliberalismo como fundamento da educação domiciliar: perspectivas para a educação no Brasil - Melo, Sthéfany Araújo (2023)
This research emerged from a concern about a proposal that has been part of the public educational debate since the 2000s with the emergence of the “Escola sem Partido” (EsP) movement but gained prominence from the 2018 elections and in the context of the government of Jair Bolsonaro. Home Education (ED), or homeschooling, is a modality of education organized and implemented by parents themselves as an alternative to schooling their children at home, and not at school, and may also use the hiring of private teachers and the acquisition of specific didactic materials. Therefore, through the postulates of a bibliographic research, the theoretical basis of this study was predominantly supported by Vasconcelos e Boto (2020), Casanova e Ferreira (2020), Araújo and Carvalho (2021), Laval (2019), Lockmann (2020) e Streeck (2012). It should be noted that, as a doctoral thesis, this work falls within the area of concentration related to work, society and education. In this way, this thesis argues that, under the arguments of the right to freedom of choice and of the school being a doctrinaire institution and partisan of certain beliefs and ideologies, homeschooling has been widespread in Brazilian society as a solution to the educational crisis, parallel to the context of gradual outsourcing/privatization of public basic education. Thus, in this study we aim to understand the relationship between the neoliberal doctrine and the educational proposal for home education. As specific objectives we proposed: a) problematize the home education project, which meets the neoliberal demand for the privatization of public education; b) analyze how the discourse of the public education crisis was constructed in the context of supposed ideological determinism, and how this thought evolved to propose the alternative of home education; c) understand neoliberalism’s concern with education; d) identify the congruences between the home education proposal and the neoliberal doctrine. With this, we proved how this proposal approaches the neoliberal ideology, whose characteristics permeate the minimal intervention of the State, the outsourcing/privatization of public institutions and the valorization of individualism. That said, we corroborate the idea of homeschooling as a business strategy, coming from the upper and dominant classes, which acts against the construction of a democratic and egalitarian project that values diversity and collectivity. Therefore, under the neoliberal prism, homeschooling is seen as a new market niche for capitalist exploitation, capable of transforming education into a very profitable commodity for those who know how to market it, and not as a process of physical and intellectual formation and development of every human being.